2023
DOI: 10.1038/s41467-023-37450-8
|View full text |Cite
|
Sign up to set email alerts
|

Neuraminidase 1 promotes renal fibrosis development in male mice

Abstract: The functions of the influenza virus neuraminidase has been well documented but those of the mammalian neuraminidases remain less explored. Here, we characterize the role of neuraminidase 1 (NEU1) in unilateral ureteral obstruction (UUO) and folic acid (FA)-induced renal fibrosis mouse models. We find that NEU1 is significantly upregulated in the fibrotic kidneys of patients and mice. Functionally, tubular epithelial cell-specific NEU1 knockout inhibits epithelial-to-mesenchymal transition, inflammatory cytoki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 63 publications
(69 reference statements)
0
4
0
Order By: Relevance
“…E-cadherin is used in the diagnosis and prognosis of epithelial cancers as reduced expression is associated with tumors undergoing EMT [ 60 ]. Moreover, other studies have shown that the increased expression of Neu-1 promotes EMT through the reduction in E-cadherin markers [ 61 , 62 ]. To determine the influence of the CB1 agonists on the expression of E-cadherin, we examined the presence and levels of E-cadherin as a marker of EMT in SW-620 colorectal cancer cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…E-cadherin is used in the diagnosis and prognosis of epithelial cancers as reduced expression is associated with tumors undergoing EMT [ 60 ]. Moreover, other studies have shown that the increased expression of Neu-1 promotes EMT through the reduction in E-cadherin markers [ 61 , 62 ]. To determine the influence of the CB1 agonists on the expression of E-cadherin, we examined the presence and levels of E-cadherin as a marker of EMT in SW-620 colorectal cancer cells.…”
Section: Resultsmentioning
confidence: 99%
“…Cells 2024, 13, x FOR PEER REVIEW 13 of 24 through the reduction in E-cadherin markers [61,62]. To determine the influence of the CB1 agonists on the expression of E-cadherin, we examined the presence and levels of Ecadherin as a marker of EMT in SW-620 colorectal cancer cells.…”
Section: Synthetic Cb1 Cannabinoids Am-404 Aravnil and Olvanil Margin...mentioning
confidence: 99%
“…In their study, Su et al ( Su et al, 2017 ) highlighted kidney resident cells, specifically podocytes secrete IL-6 under certain conditions to promote proliferation; affecting the differentiation of kidney cells. The concentration of various inflammatory signalling pathways and diseases related to inflammation in CKD patients suggests a link between CKD pathogenesis and autoimmune irregularities, a viewpoint widely accepted among CKD researchers ( Berthier et al, 2012 ; Chen et al, 2023 ). Among them, viral infections, lipids, and atherosclerosis were positively correlated with CKD, which suggests that CKD patients are prone to cardiovascular and autoimmune diseases ( Gorenjak, 2009 ; Olechnowicz-Tietz et al, 2013 ), and the development of such diseases is closely related to immune responses.…”
Section: Discussionmentioning
confidence: 99%
“…Our study found that dipsacoside B ameliorated APAP-induced hepatotoxicity by prohibiting Neu1 [ 69 ]. The newest evidence supported that salvianolic acid B show strong ability to inhibit Neu1 activity during renal fibrosis development [ 70 ]. Interfering peptides (IntPep) targeting the transmembrane (TM) domains 2 of human membrane NEU1 has been proved to disrupt NEU1 dimerization and efficiently block the sialidase activity at the plasma membrane [ 71 ].…”
Section: Neu1 Inhibitormentioning
confidence: 99%